2016
DOI: 10.1016/j.nbd.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The ADHD-linked human dopamine D4 receptor variant D4.7 induces over-suppression of NMDA receptor function in prefrontal cortex

Abstract: The human dopamine D4 receptor (hD4R) variants with long tandem repeats in the third intracellular loop have been strongly associated with attention deficit hyperactivity disorder (ADHD) and risk taking behaviors. To understand the potential molecular mechanism underlying the connection, we have investigated the synaptic function of human D4R polymorphism by virally expressing the ADHD-linked 7-repeat allele, hD4.7, or its normal counterpart, hD4.4, in the prefrontal cortex (PFC) of D4R knockout mice. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 68 publications
(86 reference statements)
1
23
0
Order By: Relevance
“…[44][45][46][47][48] The ADHD-linked human dopamine D4 receptor variant induces over-suppression of NMDAR function and aberrant regulation of synchronous network activity in PFC. 49,50 Consistent with the general finding of our current study, it has been found that overstimulation of D4 receptors in the PFC induces dysregulation of emotions reminiscent to the effects observed in schizophrenia. [51][52][53] Moreover, disruption of D4 signaling in the PFC renders animals more sensitive to stress-related conditioning memories.…”
Section: Discussionsupporting
confidence: 92%
“…[44][45][46][47][48] The ADHD-linked human dopamine D4 receptor variant induces over-suppression of NMDAR function and aberrant regulation of synchronous network activity in PFC. 49,50 Consistent with the general finding of our current study, it has been found that overstimulation of D4 receptors in the PFC induces dysregulation of emotions reminiscent to the effects observed in schizophrenia. [51][52][53] Moreover, disruption of D4 signaling in the PFC renders animals more sensitive to stress-related conditioning memories.…”
Section: Discussionsupporting
confidence: 92%
“…The different outcome of baseline mode on Conflict Effect between ADHD groups with and without medication might be explained by the effect of the stimulants [ 73 , 109 ]. The conflict (or executive control) network is mainly modulated by the dopamine system and involves brain structures in the prefrontal and anterior cingulate cortex, the anterior insula, and the basal ganglia [ 110 , 111 , 112 ]. It has been suggested that WMT might change the density of cortical dopamine receptors in the prefrontal cortex [ 113 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is in contrast to inhibition of cAMP formation, where the D4.7R response to dopamine was reported to be less potent but equally efficacious. 16 Dopamine stimulation of MAP kinase phosphorylation, mediated by G protein signaling, was similar for D4.2R, D4.4R, and D4.7R, further indicating that PLM is a signaling response that differentiates the D4.7R from D4.2R and D4.4 subtypes.…”
Section: Resultsmentioning
confidence: 80%
“…14 A higher number of repeats implies that additional proteins can associate with the D4.7R, with the potential for more diverse signaling, although the additional protein interactions can restrict D4R access to phospholipids. The D4R is bound to postsynaptic scaffolding protein-95 (PSD-95) via SH3 domain-based binding, where it modulates N -methyl- d -aspartate (NMDA) receptor function in a VNTR-dependent manner, 16 raising the possibility that the D4R may modulate synaptic function via the influence of dopamine-stimulated PLM on proteins sharing its membrane environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation